The Gold Coast Leader (September 1904) - Gold Coast Leader (The Gold Coast Leader Office, Saltpond Road, Cape Coast, 1904)
The Gold Coast Leader was a weekly newspaper that reported on local, national, and international news, with an emphasis on colonial, political, and social issues affecting the Gold Coast.
Keywords: History of Ghana; Newspaper; Gold Coast Leader Newspaper